Design and Implementation of a Risk Management System at PT. Franchise Center Indonesia - Hanny Yuliani; Tantry Yanuar Rahmat Syah; Muhammad Dhafi Iskandar; Ferryal Abadi (Cv. Utility Project Solution, 2023)
Risk management is needed to identify possible risks that exist when the business is running and protect from mitigating or tracking sources that have the potential to threaten the achievement of company goals. Other functions are to identify, analyze, and control company activities carried out by management in order to obtain higher effectiveness and efficiency. In this service PT. Franchise Center Indonesia as a service company that will become a franchise and Business Opportunity (BO) information center, wants business people or MSMEs who already have quality products and good systems that are proven to be profitable and are known more widely by the target market who wants to buy a business. The method used in this activity is to collect data, observe, analyze and evaluate the results of this activity to be able to predict the possibility and impact of risks that occur during the business so that it can be used as a guide in determining the next steps to evaluate obstacles and threats grouped according to scale. This dedication and research activity is important to maintain the continuity of its business because it will help the company remain stable and even better in its performance. The existence of risk management requires companies to establish procedures for dealing with threats, minimizing their impact, and overcoming them so that companies can make better decisions about how to develop in the future.